Sistem Informasi E-Letter Pada PT. Angkasa Pura Solusi Jakarta - Belsana ButarButar; Carlos Stepen; Muhadi H (Universitas Pradita, 2020)
PT. Angasa Pura Solusi is one of the companies engaged in airport consulting. Mail delivery system at PT. Angasa Pura Solusi is done manually by giving letters directly to employees in physical form which will be delivered directly to the place of administration. With a manual system like this, it is very inefficient and time-consuming in the process of sending mail which causes other employees to be hampered. Sometimes the letter cannot be directly received by the recipient because the person concerned is not in place, it requires additional time when the sender of the letter requires a disposition letter to the intended person. The method used in this research is the Waterfall method which is a sequential software development process, where progress is seen as continuing to flow downward (like a waterfall) through the phases of planning, modeling, implementation (construction), and testing, so as to produce E-letter application. With the construction of this E-letter website, it is expected to facilitate the process of sending mail for employees so that they do not need to come directly to the admin because it can be sent via the website and can provide convenience for employees in the process of making letters and simplify the correspondence system that aims to streamline time and can improve quality and good service at work and will be more quickly resolved quickly and accurately